Hubungan Tingkat Pendidikan Orang Tua terhadap Perilaku Sosial Anak - Rahmah, Rahmah; Armizi, Armizi; Herlinda, Susi; Fatma, Fatma (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
The level of education of parents is an order, level of education, level or order completed by parents during their education. The purpose of the study was to see the relationship between parental education and social behavior. Pre-experimental research design was conducted on 30 parents of children. The data collection technique uses a questionnaire given to the child's parents. The sample set is all parents of children. For data analysis using correlation. From the results of parents' responses to children's social behavior in terms of overall per indicator about parents' responses to children's social behavior classified as "Agree" with a percentage of 65.00%. While the level of education of parents of children who have elementary school education is 17 people with a percentage level of 56.67%, junior high school education is 9 people with a percentage of 30.00%, and high school education is 4 people with a percentage of 13.33%. The results of the above calculations show that the Produc Moment correlation value between parents' education level and children's social behavior is 0.511.